Synthesis, characterization and cytotoxicity of Pd(II) complexes for the inhibition of cathepsin B - Akinyemi, Amos Olalekan (Universidade Federal de São Carlos, 2021)
Cancer is one of the most dreaded diseases of the 20th century, and its prevalence and incidence are increasing in the 21st century. The situation is so serious that one in four people can develop cancer in their lifetime. Several components influence tumor growth, indicating multiple pathways for developing new chemotherapeutic compounds with different modes of action. The enzyme cathepsin B, for example, is related to the formation of new blood vessels that will support the tumor and tumor progression. This enzyme is overexpressed in many types of cancer, including prostate, lung, and breast cancer. In this sense, the search for compounds capable of inhibiting the action of this enzyme is extremely desirable. Palladium (II) complexes may be a promising alternative for obtaining molecules with strong cytotoxicity and the capacity to block the activity of Cathepsin B. Once they can effectively bind to the active site of the target enzyme. Hence, a thiosemicarbazone ligand and triphenylphosphine are incorporated into the molecular framework, generating compounds of the type [Pd(TSC)XPPh3] [(X = Cl-; SCN-; DMSO), PPh3 = Triphenylphosphine, TSC = 1-methyl- 3-phenylprop-2-en-1-ylidene hydrazine carbothioamide). After complete characterization of the complexes by different techniques, cytotoxicity assays were performed against three cell lines [PNT2 (non-tumor prostate cells), A2780 Cis (ovarian tumor lines), and MRC5 (non-tumor lung cells)]. The results indicate high cytotoxicity of all complexes, surpassing the value of the standard drug cisplatin by up to 1400 times. However, a preference between tumor and non-tumor cells was not noticeable. Furthermore, spectrophotometric DNA titration assays were carried out to investigate any interaction between them. The results showed weak or no interaction. Therefore, DNA was ruled out as a possible cytotoxic target. Nevertheless, from the topoisomerase inhibition assay, it was possible to observe the ability to prevent DNA relaxation caused by the topoisomerase I beta enzyme, indicating that this may be one of the pharmacological targets of these complexes. Additionally, the compounds were shown to irreversibly inhibit the action of cathepsin B at concentrations lower than 100 uM. Therefore, it is concluded that this type of compound can present interesting structural characteristics to provide metallic compounds that inhibit cancer progression.
Síntese, caracterização e citotoxicidade de complexos de Pd (II) para a inibição da catepsina B
Keywords: Catepsina B; Câncer; Composto de Paládio; Citotoxicidade; Cathepsin B; Cancer; Palladium compound; Cytotoxicity; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA